Characteristics of Leaders in the Qur'an ( Interpretation of QS. Al-Qasas [28]: 85-88 Ma'na-Cum-Maghza Perspective) - Aty Munshihah; Nurun Nisaa Baihaqi (UIN Sulthan Thaha Saifuddin Jambi, 2022)
Some readers make QS. Al-Qasas [28]: 85 as the argument for going home or returning home. This can be seen by the presence of posts from one of the official accounts of millennial youth preaching @quranreview on Instagram. The indicator for returning home cannot be separated from the ma'ad vocabulary, which means a place to return. Even so, it is necessary to look again at the entire verse, because the context that has not been read is in the form of the da'wah context in it . Because of this, a re-examination is needed starting from the syntagmatics, the munasabah, to the context of the verse, so that an increasingly broad meaning can be found. By using the ma'na-cum-maghza approach which in its steps does not only look at the conditions when the verse was revealed ( maghza at-tarikhi) but also involves dynamic changes to the present ( maghza al-mutaharrik ), it can be seen that the verse studied not only interpreted by the process of traveling to a place of return but much broader than that. The results of this research include that this verse does not only talk about returning home but is related to the behavior of preachers as well as leaders . Leaders who can provide a guarantee of a safe life because they have carried out their mandate by carrying out orders according to the rules without defending wrong or justifying false cases as determined by law.